In-plane stiffness of traditional timber floors strengthened with CLT - Branco, Jorge M. (2014)
Five full-scale timber floors were tested in order to analyze the in-plane behaviour of these structural systems. The main objective was to assess the effectiveness of the in-plane strengthening using cross laminated timber (CLT). For that, one unstrengthened specimen (original), one specimen strengthened with a second wood board, two specimens strengthened with 3 CLT panels and one specimen strengthened with 2 CLT panels were tested. Moreover, because of its importance in the composite behaviour, the first phase of the experimental program was composed by push-out tests on specimens representing the shear connection between the timber beams and the CLT panels. This paper describes the tests performed and the numerical modelling aimed to evaluate the composite behaviour of the strengthened timber floors.